THE INFLUENCE OF CAMEL FINANCIAL RATIO IN PREDICTING POTENTIAL FINANCIAL DISTRESS IN BANKING COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE 2019-2022 - Kurniyawati, Indah; Ghofur, Abdul; Rosdiyati, Rosdiyati; Jannah, Fitri Nur; Safitri, Nilla (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
This research was conducted with the aim of determining the effect of the CAMEL ratio on predicting potential financial distress in banking companies listed on the Indonesia Stock Exchange. The CAMEL ratio is presented using the variables capital adequacy ratio (CAR), operational costs to operating income (BOPO), return on assets (ROA), return on equity (ROE), non-performing loans (NPL), and loan to deposit ratio ( LDR). Sampling in this study used a purposive sampling method, with a total population of 46 banking companies listed on the Indonesian Stock Exchange for the 2019-2022 period. From this population, 25 banking companies were obtained as research samples. The data analysis method used is the coefficient of determination method and partial test. The results of this research show that CAR, BOPO, ROA, ROE, partially do not have a significant effect on financial distress, while for the NPL variable, LDR has a significant positive effect on financial distress conditions in banking companies listed on the Indonesian Stock Exchange.